2010
DOI: 10.4236/ns.2010.210141
|View full text |Cite
|
Sign up to set email alerts
|

Correlated mutations in the four influenza proteins essential for viral RNA synthesis, host adaptation, and virulence: NP, PA, PB1, and PB2

Abstract: The NP, PA, PB1, and PB2 proteins of influenza viruses together are responsible for the transcription and replication of viral RNA, and the latter three proteins comprise the viral polymerase. Two recent reports indicated that the mutation at site 627 of PB2 plays a key role in host range and increased virulence of influenza viruses, and could be compensated by multiple mutations at other sites of PB2, suggesting the association of this mutation with those at other sites. The objective of this study was to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Site PB2_627 in avian H5N1 was connected to PB2_ 649 and PB2_451 that belonged to a group of mutu nnected sites, thereby revealing several potential sites sites in PB1, PA, and NP of human H5N1 (Figure 7). Importantly, here PB2_524 actually was a hub site that connected many sites in PB2 of human H5N1, including site PB2_590, one of the two sites of SR polymorphism discovered in [40] that could enhance polymerase activity in human cells. The connection between PB2_590 and PB2_524 in human H5N1 suggested that the change at site 590 might be associated with the change at site 524, as well as other sites connected by site 524, which enlarged the number of potential sites that might influence site 590.…”
Section: Correlated Site Pairs In Pb2 Prmentioning
confidence: 93%
See 1 more Smart Citation
“…Site PB2_627 in avian H5N1 was connected to PB2_ 649 and PB2_451 that belonged to a group of mutu nnected sites, thereby revealing several potential sites sites in PB1, PA, and NP of human H5N1 (Figure 7). Importantly, here PB2_524 actually was a hub site that connected many sites in PB2 of human H5N1, including site PB2_590, one of the two sites of SR polymorphism discovered in [40] that could enhance polymerase activity in human cells. The connection between PB2_590 and PB2_524 in human H5N1 suggested that the change at site 590 might be associated with the change at site 524, as well as other sites connected by site 524, which enlarged the number of potential sites that might influence site 590.…”
Section: Correlated Site Pairs In Pb2 Prmentioning
confidence: 93%
“…Despite intense research on H5N1, further understanding of the molecular mechanisms for avian influenza virus to cross species boundaries to infect humans is of major interest. Using the computational methodology developed in [14][15][16][17][18][19][20][21][22][23][24], the current proteomic study aimed to discover molecular characteristics in the proteins of avian and human H5N1 viruses in Asia and to identify viral traits including HA binding features that might promote the transmission of H5N1 from birds to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the work in [1], which used three 2013 H7N9 strains collected from three patients in China, this study employed the methodology developed in [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] to investigate this novel avian-origin H7N9 virus with five 2013 H7N9 strains in China. Our aim was to discover gene sequence difference between this new virus and the previous avian H7N9 and identify and then analyze mutations in the HA protein that could help this virus making its adaptation from avian to human hosts.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the emergence of this novel H7N9 virus in China, we were very curious to learn, employing the methodology developed in [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], the individual as well as the collective impact of the mutations identified in [4,6] on the receptor selection of H5N1. At the same time, beyond the groups of HA mutations examined in these two studies we wanted to seek other possible groups of mutations that could render similar effect on HA receptor binding preference to those found in [4,6].…”
Section: Introductionmentioning
confidence: 99%